Long-term effectiveness of enzyme replacement therapy in Fabry disease with the p.Arg227Ter variant: Fabry disease in Ostrobothnia (FAST) study - Pietilä-Effati Päivi; Saarinen Jukka T; Löyttyniemi Eliisa; Saarenhovi Maria; Autio Reijo; Kantola Ilkka (Wiley, 2025)
Fabry disease (FD) is an X chromosome-linked, life-threatening lysosomal disease caused by one of more than 1000 currently known variants in the α-galactosidase A (GLA) gene. The follow-up part of the Fabry Disease in Ostrobothnia (FAST) study reports the long-term effect of enzyme replacement therapy (ERT) on a prospectively collected cohort of 12 patients, 4 males and 8 females, mean age 46 years (SD 16), with the classical variant c.679C > T p.Arg227Ter, which is one of the most common FD variants worldwide. In the natural history period of the FAST study, half of the patients in both sexes had at least one major event, of which 80% were of cardiac origin. During 5 years of ERT, four patients had a total of six major clinical events consisting of one silent ischemic stroke, three ventricular tachycardias and two increased left ventricular mass indexes. In addition, four patients developed minor cardiac events, four patients minor renal events, and one patient a minor neurological event. ERTs may delay but not prevent the progression of the disease in most patients with the variant Arg227Ter. This variant might be suitable for investigating the efficacy of second-generation ERTs compared to the currently used ERTs regardless of sex.